2013
DOI: 10.1002/etc.2359
|View full text |Cite|
|
Sign up to set email alerts
|

What's causing toxicity in sediments? Results of 20 years of toxicity identification and evaluations

Abstract: Sediment toxicity identification and evaluation (TIE) methods have been used for 20 yr to identify the causes of toxicity in sediments around the world. In the present study, the authors summarize and categorize results of 36 peer-reviewed TIE studies (67 sediments) into nonionic organic, cationic, ammonia, and "other" toxicant groups. Results are then further categorized according to whether the study was performed in freshwater or marine sediments and whether the study was performed using whole-sediment or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 84 publications
(81 reference statements)
3
20
0
Order By: Relevance
“…However, ΣH 2 S and dissolved Fe(II) displayed an inverse pattern ( p = 0.092, r =–0.23; Figure ), such that high ΣH 2 S (>20 µM) never co‐occurred with high dissolved Fe(II) (>200 µM) in the same porewater sample. We observed ΣH 2 S concentrations higher than 5 µM, the concentration known to be toxic to some plants , in 10 of the 54 porewater samples.…”
Section: Case Study Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, ΣH 2 S and dissolved Fe(II) displayed an inverse pattern ( p = 0.092, r =–0.23; Figure ), such that high ΣH 2 S (>20 µM) never co‐occurred with high dissolved Fe(II) (>200 µM) in the same porewater sample. We observed ΣH 2 S concentrations higher than 5 µM, the concentration known to be toxic to some plants , in 10 of the 54 porewater samples.…”
Section: Case Study Resultsmentioning
confidence: 75%
“…same porewater sample. We observed SH 2 S concentrations higher than 5 mM, the concentration known to be toxic to some plants [65], in 10 of the 54 porewater samples. Porewater SNH 4 þ concentrations ranged from 0.2 mM to 1170 mM (2.5-16 440 mg N L À1 ), with a mean of 195 mM (2730 mg N L À1 ) and median of 50.6 mM.…”
Section: Sulfidementioning
confidence: 75%
“…The contribution of nonionized ammonia to the toxicity in interstitial water toxicity tests and sediment TIE has been extensively reported . Ho and Burgess recently reviewed sediment TIE studies and found that ammonia contributed to interstitial water toxicity in 31% of the studies analyzed. Ammonia can be naturally found in sediments and, as was discussed earlier, it is usually considered to be a confounding factor in sediment toxicity tests .…”
Section: Discussionmentioning
confidence: 99%
“…Ho and Burgess (2013) reviewed 30 marine and freshwater sediment TIEs over a 20-yr time span and found that approximately 90% of studies identified a nonpolar organic as a source of toxicity in sediments, with 70% of evaluations characterizing nonpolar organics as the sole source of toxicity. Ho and Burgess (2013) reviewed 30 marine and freshwater sediment TIEs over a 20-yr time span and found that approximately 90% of studies identified a nonpolar organic as a source of toxicity in sediments, with 70% of evaluations characterizing nonpolar organics as the sole source of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The need for reducing false-negatives when working with nonpolar organics amendments becomes even more apparent when considering the likelihood of a nonpolar organic contributing to the risk in contaminated sediments. Ho and Burgess (2013) reviewed 30 marine and freshwater sediment TIEs over a 20-yr time span and found that approximately 90% of studies identified a nonpolar organic as a source of toxicity in sediments, with 70% of evaluations characterizing nonpolar organics as the sole source of toxicity. Because nonpolar organics are one of the key classes causing toxicity, understanding the limitations and working to improve the use of activated carbon or powdered coconut charcoal are critical.…”
Section: Introductionmentioning
confidence: 99%